Analysis of Creative Thinking Abilities of Prospective Mathematics Teachers in Solving and Posing Quadrilateral Open-ended Problems - Jovitha Indah Gisbtarani; Veronika Fitri Rianasari (Universitas Sarjanawiyata Tamansiswa, 2021)
Prospective teachers are required to develop their creative thinking abilities. The creative thinking abilities can help prospective teachers in designing the learning process, one of which is in designing non-routine problems as an evaluation of learning. This study aims to describe the creative thinking abilities of six sixth-semester students of Mathematics Education at Sanata Dharma University in solving and posing open-ended problems on the topic of quadrilateral. Data collection methods used are written tests to solve and pose open-ended problems and interviews. Data analysis adopted the framework of qualitative data analysis namelyÂ data reduction,Â data display, andÂ conclusion drawing. The results showed that (1) the students' creative thinking abilities in solving open-ended quadrilateral problems were categorized into four categories namely very poor (1 student), poor (3 students), fair (2 students) and good (1 student), (2) the students' creative thinking abilities in posing open-ended quadrilateral problems were categorized into three categories of creative thinking abilities namely very poor (2 students), poor (1 student) and very good (3 students).